Super-flexible ceramic fiber based on ceramic precursor and preparation process of super-flexible ceramic fiber

Through the preparation process based on ceramic precursors, electrospinning and surface modification technology, the shortcomings of ceramic nanofibers in mechanical properties and high temperature resistance are solved, and the preparation of ultra-flexible ceramic fibers is realized, with excellent mechanical properties and heat resistance.

CN119640437APending Publication Date: 2025-03-18吉祥三宝高科新材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411811592.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing ceramic nanofibers have shortcomings in mechanical properties and high temperature resistance, and are difficult to meet the needs of higher flexibility and heat resistance.

Method used

The ceramic precursor fiber is prepared by electrospinning technology, and the crosslinked structure and metal components of the fiber are added through surface modification and electrochemical plating to form ultra-flexible ceramic fibers.

Benefits of technology

It significantly improves the mechanical properties and heat resistance of ceramic fibers, enhances the mechanical properties and electrical conductivity of the fibers, and is suitable for applications in high temperature environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a super-flexible ceramic fiber based on a ceramic precursor and a preparation process of the super-flexible ceramic fiber, and belongs to the technical field of fiber materials. The invention relates to a super-flexible ceramic fiber based on a ceramic precursor, the super-flexible ceramic fiber comprises aluminum and silicon, and the molar ratio of the aluminum to the silicon is (1.4-2): (1.4-1.8); the super-flexible ceramic fiber further comprises copper and gold. The preparation method comprises the following steps: uniformly mixing raw materials, adjusting pH, and stirring to obtain precursor sol; secondly, dipping the precursor sol in a silica sol solution, freezing and fixing with nitrogen, and freeze-drying; and finally, plating metal, calcining and cooling to obtain the super-flexible ceramic fiber. The super-flexible ceramic fiber prepared through testing has good mechanical performance and softness, still has good conductivity and heat resistance after high-temperature treatment, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber materials, and in particular relates to an ultra-flexible ceramic fiber based on a ceramic precursor and a preparation process thereof. Background Art

[0002] Ceramic fibers have advantages such as large aspect ratio and continuity. When subjected to stress, stress can be diffused axially to avoid brittle fracture caused by stress concentration. They are expected to withstand large external stresses, thereby significantly improving the flexibility of ceramic materials. Current methods for preparing ceramic fibers include centrifugal, dry spinning, electrospinning and other technologies. Among them, electrospinning technology can prepare nano-sized ceramic nanofiber materials, which can further improve the strength, toughness and flexibility of ceramic fiber materials based on the size effect. In addition, this technology has the advantages of simple process, strong universality and low energy consumption. It has obvious advantages in large-scale production and has become the main method for preparing ceramic nanofibers.

[0003] The patent application with publication number CN 116163040 A discloses a method for preparing flexible titanium dioxide ceramic nanofiber yarn: a titanium dioxide precursor solution is prepared by a sol-gel method, the spinning solution is transferred to two syringes for tip conjugated electrospinning to obtain a precursor nanofiber yarn; the precursor nanofiber yarn is placed in an oven to dry to remove residual solvent, and then calcined in an air atmosphere by a step-by-step heating method to obtain a flexible titanium dioxide ceramic nanofiber yarn. Although the ceramic nanofiber yarn prepared in this application has good acid and alkali resistance and heat resistance, its mechanical properties and high temperature resistance need to be improved. Summary of the invention

[0004] The object of the present invention is to provide an ultra-flexible ceramic fiber based on a ceramic precursor and a preparation process thereof, so as to improve the mechanical properties of the flexible ceramic fiber.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An ultra-flexible ceramic fiber based on a ceramic precursor, wherein the ultra-flexible ceramic fiber comprises aluminum and silicon, and the molar ratio of the aluminum to silicon is 1.4-2:1.4-1.8;

[0007] The ultra-flexible ceramic fiber also includes copper and gold.

[0008] An ultra-flexible ceramic fiber based on a ceramic precursor and a preparation process thereof, comprising the following steps:

[0009] (1) adding 1 mol / L nitric acid solution, vinyl trimethylsiloxane, Al(NO3)3·9H2O and AIP (aluminum isopropoxide) to a 10 wt% PVP (polyvinyl pyrrolidone) / water solution, adjusting the pH with C2H2O4 (anhydrous oxalic acid), and stirring for 12 to 14 hours to obtain a polyaluminosiloxane precursor sol;

[0010] (2) electrospinning the precursor sol, fully impregnating the silica sol solution, freezing and fixing with nitrogen, and freeze-drying to obtain ceramic precursor fibers;

[0011] (3) The ceramic precursor fiber is surface-modified with a Tris (trishydroxymethylaminomethane) aqueous solution containing a high molecular weight polymer and 0.01 mol / L dopamine hydrochloride; then, it is immersed in a catalyst of 0.003 mol / L ammonium chloropalladate aqueous solution and placed in a dark environment to react for 0.5 to 1 hour; then, it is placed in a copper ion and gold ion chemical plating solution in turn to react for 2 to 3 hours, calcined, and naturally cooled to obtain an ultra-flexible ceramic fiber.

[0012] Furthermore, the dosage ratio of the nitric acid solution, vinyl trimethylsiloxane, Al(NO3)3·9H2O, AIP and PVP / water solution is 2.5-3 mL: 2-3 g: 1-1.2 g: 2-2.5 g: 40-50 mL; and the pH is adjusted to 1-2.

[0013] Other strong acids, such as hydrochloric acid, concentrated sulfuric acid and nitric acid, are not easy to adjust the pH value and are easy to volatilize. C2H2O4 can gently adjust the pH of the sol system and maintain the stability of the system. It can also be removed by calcination without producing other by-products. Therefore, the present invention selects C2H2O4 to adjust the pH of the sol system.

[0014] Furthermore, the electrospinning parameters are as follows: ambient humidity is 30-40%, ambient temperature is 15-25° C., spinning rate is 1.5 mL / hr, spinning distance is 15-20 cm, and spinning voltage is 15-20 kV.

[0015] Furthermore, the preparation method of the silica sol solution is as follows:

[0016] Mix 5-6 g TEOS, 20-25 mL ethanol, 2.8-3 mL C2H2O4 and 500-750 mL H2O, and stir for 1-1.5 h to obtain a silica sol solution.

[0017] Furthermore, the mass ratio of the high molecular weight polymer to dopamine hydrochloride is 1:1, the pH of the Tris aqueous solution of dopamine hydrochloride is 8 to 10; and the modification treatment time is 22 to 24 hours.

[0018] Furthermore, the high molecular polymer includes one or a combination of polyvinyl pyrrolidone, polyethylene imine, polyethylene oxide, polyvinyl alcohol and polyvinyl butyral.

[0019] Furthermore, the calcination temperature is 900-910° C., the heating rate is 5-6° C. / min, and the temperature is raised to 900-910° C. and maintained for 1-1.5 hours.

[0020] Beneficial effects of the present invention:

[0021] (1) The ultra-flexible ceramic fiber prepared by the present invention adopts high-temperature resistant silica sol, which plays a bonding role, so that cross-linking points appear between two fibers, and the cross-linking structure between the fibers makes the irregular entanglement state of the fibers more severe, thereby improving the mechanical properties and heat resistance of the ceramic fiber.

[0022] (2) The present invention adopts Al 3+ Dissolves in water and undergoes hydrolysis to generate Al(OH) 4- Get a lot of H + , providing an acidic environment, Al(OH) 4- With the original Al 3+ Combined to form -Al-O- structure, the original NO 3- The sol particles can be adsorbed to each other, so that the sol system is maintained in a stable state. The silicon source is hydrolyzed into a Si-OH structure, which is polycondensed into an O-Si-O structure under acidic conditions. The acidic environment formed by adjusting the pH of C2H2O4 promotes the hydrolysis and polycondensation of AIP, thereby also generating an -Al-O- structure. The -Al-O- structure and the O-Si-O structure undergo a condensation reaction to generate an Al-O-Si structure. In addition, the present invention selects a soluble aluminum salt instead of an aluminum silicate, and uses water as a solvent instead of an organic solvent, thereby reducing environmental pollution and consumables costs. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] This embodiment provides an ultra-flexible ceramic fiber based on a ceramic precursor, which is prepared by the following steps:

[0026] (1) 2.5 mL of 1 mol / L nitric acid solution, 2 g of vinyl trimethylsiloxane, 1 g of Al(NO3)3·9H2O, and 2.5 g of AIP were added to 40 mL of 10 wt% PVP / water solution, the pH was adjusted to 1 with C2H2O4, and the mixture was stirred for 12 h to obtain a polyaluminosiloxane precursor sol.

[0027] (2) 6 g of TEOS, 25 mL of ethanol, 3 mL of C2H2O4 and 500 mL of H2O were mixed and stirred for 1 h to obtain a silica sol solution;

[0028] The precursor sol is subjected to electrospinning (electrospinning parameters are as follows: ambient humidity of 30-40%, ambient temperature of 15-25°C, spinning rate of 1.5 mL / hr, spinning distance of 15-20 cm, spinning voltage of 15-20 kV), fully impregnated with silica sol solution, frozen and fixed with nitrogen, and freeze-dried to obtain ceramic precursor fibers;

[0029] (3) The ceramic precursor fiber was surface-modified with a Tris aqueous solution containing polyethyleneimine and 0.01 mol / L dopamine hydrochloride (the mass ratio of polyethyleneimine to dopamine hydrochloride was 1:1) for 24 h; then, it was immersed in a catalyst of 0.003 mol / L ammonium chloropalladate aqueous solution and allowed to react in a dark environment for 1 h; it was placed in a chemical plating solution of copper sulfate pentahydrate and potassium chloroaurate in turn for ion chelation and reduction reactions, with reaction times of 0.5 h and 2 h, respectively; then, it was calcined at 900 °C with a heating rate of 6 °C / min, the temperature was raised to 900 °C and maintained for 1.5 h, and then naturally cooled to obtain an ultra-flexible ceramic fiber.

[0030] Example 2

[0031] The present embodiment differs from the embodiment 1 in that "2 g vinyl trimethylsiloxane, 1 g Al(NO3)3·9H2O, 2.5 g AIP" in (1) is changed to "3 g vinyl trimethylsiloxane, 1.2 g Al(NO3)3·9H2O, 2.5 g AIP".

[0032] The remaining raw materials and preparation process remain the same as in Example 1.

[0033] Example 3

[0034] The present embodiment differs from the embodiment 1 in that "2 g vinyl trimethylsiloxane, 1 g Al(NO3)3·9H2O, 2.5 g AIP" in (1) is changed to "2.5 g vinyl trimethylsiloxane, 1.2 g Al(NO3)3·9H2O, 2 g AIP".

[0035] The remaining raw materials and preparation process remain the same as in Example 1.

[0036] Example 4

[0037] The difference between this embodiment and embodiment 1 is that the pH in (1) is adjusted to 2.

[0038] The remaining raw materials and preparation process remain the same as in Example 1.

[0039] Example 5

[0040] The difference between this embodiment and embodiment 1 is that "500 mL H2O" in (2) is changed to "750 mL H2O".

[0041] The remaining raw materials and preparation process remain the same as in Example 1.

[0042] Example 6

[0043] The difference between this embodiment and embodiment 1 is that the "polyethyleneimine" in (2) is replaced by "polyvinyl pyrrolidone".

[0044] The remaining raw materials and preparation process remain the same as in Example 1.

[0045] Example 7

[0046] The difference between this embodiment and embodiment 1 is that no metal plating operation is performed in (3). The specific implementation steps are as follows:

[0047] (3) calcining at 900°C with a heating rate of 6°C / min, heating to 900°C and maintaining for 1.5 h, and then cooling naturally to obtain ultra-flexible ceramic fibers.

[0048] The remaining raw materials and preparation process remain the same as in Example 1.

[0049] Comparative Example 1

[0050] The difference between this comparative example and Example 1 is that the pH in (1) is adjusted to 3.

[0051] The remaining raw materials and preparation process remain the same as in Example 1.

[0052] Comparative Example 2

[0053] The difference between this comparative example and Example 1 is that "500 mL H2O" in (2) is changed to "250 mL H2O".

[0054] The remaining raw materials and preparation process remain the same as in Example 1.

[0055] Comparative Example 3

[0056] Compared with Example 1, the difference between this comparative example and Example 1 is that no copper plating operation is performed in (3). The specific implementation steps are as follows:

[0057] (3) The ceramic precursor fiber was surface-modified with a Tris aqueous solution containing polyethyleneimine and 0.01 mol / L dopamine hydrochloride (the mass ratio of polyethyleneimine to dopamine hydrochloride was 1:1) for 24 hours; then immersed in a catalyst of 0.003 mol / L ammonium chloropalladate aqueous solution and placed in a dark environment for reaction for 1 hour; placed in a chemical plating solution of potassium chloroaurate for ion chelation and reduction reaction for 2 hours; then calcined at 900°C with a heating rate of 6°C / min, heated to 900°C and maintained for 1.5 hours, and cooled naturally to obtain an ultra-flexible ceramic fiber. The remaining raw materials and preparation process remain the same as in Example 1.

[0058] The remaining raw materials and preparation process remain the same as in Example 1.

[0059] Comparative Example 4

[0060] Compared with Example 1, the difference between this comparative example and Example 1 is that no gold plating operation is performed in (3). The specific implementation steps are as follows:

[0061] (3) The ceramic precursor fiber was surface-modified with a Tris aqueous solution containing polyethyleneimine and 0.01 mol / L dopamine hydrochloride (the mass ratio of polyethyleneimine to dopamine hydrochloride was 1:1) for 24 h; then, it was immersed in a catalyst of 0.003 mol / L ammonium chloropalladate aqueous solution and reacted in a dark environment for 1 h; it was placed in a chemical plating solution of copper sulfate pentahydrate for ion chelation and reduction reaction, and the reaction time was 0.5 h; then, it was calcined at 900°C with a heating rate of 6°C / min, the temperature was raised to 900°C and maintained for 1.5 h, and the temperature was naturally cooled to obtain an ultra-flexible ceramic fiber.

[0062] The remaining raw materials and preparation process remain the same as in Example 1.

[0063] Comparative Example 5

[0064] The only difference between this comparative example and comparative example 4 is that high-temperature calcination is not performed after copper plating in (3). The specific implementation steps are as follows:

[0065] (1) 2.5 mL of 1 mol / L nitric acid solution, 2 g of vinyl trimethylsiloxane, 1 g of Al(NO3)3·9H2O, and 2.5 g of AIP were added to 40 mL of 10 wt% PVP / water solution, the pH was adjusted to 1 with C2H2O4, and the mixture was stirred for 12 h to obtain a polyaluminosiloxane precursor sol.

[0066] (2) 6 g of TEOS, 25 mL of ethanol, 3 mL of C2H2O4 and 500 mL of H2O were mixed and stirred for 1 h to obtain a silica sol solution;

[0067] The precursor sol was electrospun (electrospinning parameters were as follows: ambient humidity of 30-40%, ambient temperature of 15-25°C, spinning rate of 1.5 mL / hr, spinning distance of 15-20 cm, spinning voltage of 15-20 kV), fully impregnated with silica sol solution, nitrogen frozen and fixed, freeze-dried, and then calcined at 900°C, with a heating rate of 6°C / min, heated to 900°C and maintained for 1.5 hours, and cooled naturally to obtain ceramic precursor fibers;

[0068] (3) The ceramic precursor fiber was surface-modified with a Tris aqueous solution containing polyethyleneimine and 0.01 mol / L dopamine hydrochloride (the mass ratio of polyethyleneimine to dopamine hydrochloride was 1:1) for 24 hours; then, it was immersed in a catalyst of 0.003 mol / L ammonium chloropalladate aqueous solution and allowed to react in a dark environment for 1 hour; it was placed in a copper sulfate pentahydrate chemical plating solution for ion chelation and reduction reaction, and the reaction time was 0.5 hours; and an ultra-flexible ceramic fiber was obtained.

[0069] Comparative Example 6

[0070] Compared with Example 1, the difference between this comparative example is that the aluminum source is replaced with the silicon source of the same molar amount, and the specific implementation steps are as follows:

[0071] (1) 2.5 mL of 1 mol / L nitric acid solution and 4.5 g of vinyl trimethylsiloxane were added to 40 mL of 10 wt % PVP / water solution, the pH was adjusted to 1 with C2H2O4, and the mixture was stirred for 12 h to obtain a polysiloxane precursor sol.

[0072] The remaining raw materials and preparation process remain the same as in Example 1.

[0073] Performance tests were carried out on Examples 1 to 7 and Comparative Examples 1 to 6. The average diameter of the fiber was tested using SEM; the softness was tested using a softness tester; the tensile strength of the fiber was tested using a dynamic thermomechanical analyzer; and the electronic conductivity was tested using a four-probe method.

[0074] The results are shown in Table 1:

[0075] Table 1

[0076] project Average diameter(nm) Softness(mN) Tensile strength(kPa) Conductivity (S / m) Example 1 290 13 8.72 <![CDATA[1.12*10 5 ]]> Example 2 295 15 8.61 <![CDATA[1.10*10 5 ]]> Example 3 295 14 8.58 <![CDATA[1.11*10 5 ]]> Example 4 300 18 8.41 <![CDATA[1.11*10 5 ]]> Example 5 310 22 8.30 <![CDATA[1.10*10 5 ]]> Example 6 330 25 8.35 <![CDATA[1.08*10 5 ]]> Example 7 285 14 8.36 <![CDATA[0.02*10 5 ]]> Comparative Example 1 320 24 8.27 <![CDATA[1.04*10 5 ]]> Comparative Example 2 280 28 7.79 <![CDATA[1.01*10 5 ]]> Comparative Example 3 320 18 8.35 <![CDATA[0.02*10 5 ]]> Comparative Example 4 310 20 8.11 <![CDATA[0.02*10 5 ]]> Comparative Example 5 305 21 8.40 <![CDATA[1.04*10 5 ]]> Comparative Example 6 330 30 7.40 <![CDATA[1.02*10 5 ]]>

[0077] It can be seen from Table 1 that, compared with Example 1, Examples 2 to 3 and 6 are merely adjustments or replacements of raw materials and raw material ratios within the allowable range, which have little effect on the final performance of the ceramic fiber; Compared with Example 1, Example 4 and Comparative Example 1 have a larger pH adjustment range, and the results show that the lower the pH, the better the mechanical properties (softness, tensile strength) of the ceramic fiber. This is because during the electrospinning process, the increase in the degree of protonation will lead to a decrease in the repulsive Coulomb force between colloids, causing the colloidal particles to aggregate, which is beneficial to the final fiber formation; Compared with Example 1, Example 5 and Comparative Example 2 differ in the concentration of the silica sol solution. The lower the concentration, the worse the cross-linking effect. However, when the concentration increases to a certain level, the silica ash blocks the pores of the fiber aggregate, resulting in reduced mechanical properties of the ceramic fiber.

[0078] Comparing Comparative Examples 3 to 5 and Example 7 with Example 1, it can be concluded that copper mainly plays a role in improving conductivity in the system, but it is easily oxidized and loses conductivity at high temperatures. The present invention adopts a gold plating process to protect it. The prepared ceramic fiber not only has good conductivity at high temperatures, but the ductility of the metal also improves the tensile properties of the ceramic fiber and has good softness. Compared with Example 1, the difference in Comparative Example 6 is that the aluminum source is replaced with the same molar amount of silicon source, the interaction between aluminum and silicon disappears, and the mechanical properties are greatly reduced.

[0079] In summary, the present invention provides an ultra-flexible ceramic fiber based on a ceramic precursor and its preparation process. The prepared ultra-flexible ceramic fiber has good mechanical properties and softness, still has good electrical conductivity after high-temperature treatment, has good heat resistance, and has good application prospects.

[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An ultra-flexible ceramic fiber based on a ceramic precursor, characterized in that: The ultra-flexible ceramic fiber comprises aluminum and silicon, and the molar ratio of the aluminum to silicon is 1.4-2:1.4-1.

8.

2. An ultra-flexible ceramic fiber based on a ceramic precursor, characterized in that: The ultra-flexible ceramic fiber also includes copper and gold.

3. A process for preparing ultra-flexible ceramic fibers based on ceramic precursors as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: (1) adding 1 mol / L nitric acid solution, vinyl trimethylsiloxane, Al(NO3)3·9H2O and AIP to a 10 wt% PVP / water solution, adjusting the pH with C2H2O4, and stirring for 12 to 14 h to obtain a polyaluminosiloxane precursor sol; (2) electrospinning the precursor sol, fully impregnating the silica sol solution, freezing and fixing with nitrogen, and freeze-drying to obtain ceramic precursor fibers; (3) The ceramic precursor fiber is surface-modified with a Tris aqueous solution containing a high molecular weight polymer and 0.01 mol / L dopamine hydrochloride; then, it is immersed in a catalyst of a 0.003 mol / L ammonium chloropalladate aqueous solution and placed in a dark environment to react for 0.5 to 1 hour; then, it is placed in a chemical plating solution of copper ions and gold ions in turn to react for 2 to 3 hours, calcined, and naturally cooled to obtain an ultra-flexible ceramic fiber.

4. The process for preparing ultra-flexible ceramic fiber based on ceramic precursor according to claim 3, characterized in that: The dosage ratio of the nitric acid solution, vinyl trimethylsiloxane, Al(NO3)3·9H2O, AIP and PVP / water solution is 2.5-3 mL: 2-3 g: 1-1.2 g: 2-2.5 g: 40-50 mL; the pH is adjusted to 1-2.

5. The process for preparing ultra-flexible ceramic fiber based on ceramic precursor according to claim 3, characterized in that: The electrospinning parameters are as follows: ambient humidity is 30-40%, ambient temperature is 15-25° C., spinning rate is 1.5 mL / hr, spinning distance is 15-20 cm, and spinning voltage is 15-20 kV.

6. The process for preparing ultra-flexible ceramic fiber based on ceramic precursor according to claim 3, characterized in that: The preparation method of the silica sol solution is as follows: Mix 5-6 g TEOS, 20-25 mL ethanol, 2.8-3 mL C2H2O4 and 500-750 mL H2O, and stir for 1-1.5 h to obtain a silica sol solution.

7. The process for preparing ultra-flexible ceramic fiber based on ceramic precursor according to claim 3, characterized in that: The mass ratio of the high molecular weight polymer to dopamine hydrochloride is 1:1, the pH of the Tris aqueous solution of dopamine hydrochloride is 8-10; and the modification treatment time is 22-24 hours.

8. The process for preparing ultra-flexible ceramic fiber based on ceramic precursor according to claim 3, characterized in that: The high molecular polymer includes one or a combination of polyvinyl pyrrolidone, polyethylene imine, polyethylene oxide, polyvinyl alcohol and polyvinyl butyral.

9. The process for preparing ultra-flexible ceramic fiber based on ceramic precursor according to claim 3, characterized in that: The calcination temperature is 900-910° C., the heating rate is 5-6° C. / min, and the temperature is raised to 900-910° C. and maintained for 1-1.5 hours.

Citation Information

Patent Citations

  • Preparation method of flexible titanium dioxide ceramic nanofiber yarn

    CN116163040A